Research on monitoring and stability evaluation of ground subsidence in gypsum mine goaf - Xu, Zaicheng; Xu, Wei; Zhu, Zhenhua; Zhao, Junyi (Frontiers in Environmental Science, 2023)
The geological disasters caused by the ground deformation of the goaf have brought huge security risks to the ecological environment and society. Therefore, it is imminent to realize the effective monitoring and stability analysis of the ground deformation of the goaf. In this paper, taking the goaf of the gypsum mine in Diaodao District, Jingmen City as an example, through the investigation of the overall structure and distribution characteristics of the gypsum goaf, combined with the mechanical parameters of the rock mass selected from the site, the InSAR and GNSS technology are used to analyze the ground of the goaf of the gypsum mine. Deformation monitoring is carried out to give full play to the advantages of InSAR monitoring with high vertical accuracy and GNSS monitoring with high horizontal accuracy. Analyzed the thickness conditions of the mined-out area of pillar, roof and overlying rock, established the numerical model of the goaf, and used FLAC (3D) to carry out numerical simulation on this basis to evaluate the stability of the goaf. The research shows that two subsidence areas and three deformation areas were deciphered by DInSAR and time series InSAR, respectively, and the deep buried areas in the goaf were monitored by GNSS. The surface deformation is dominated by horizontal displacement, and the direction of horizontal displacement is The whole points to the goaf. Finally, based on the conclusion that the gob is in different degrees of deformation, the stability of the gob is analyzed, and the area of surface subsidence is obtained by FLAC (3D) simulation.